KESETARAAN DALAM PENGAMBILAN KEPUTUSAN DAN TINGKAT KEPEMILIKAN BARANG BERHARGA ASN PEREMPUAN DI KOTA DENPASAR - Yulia Dewi, Putu Eka; Marhaeni, A. A. I. N (E-Jurnal Ekonomi Pembangunan Universitas Udayana, 2021)
The objectives in this study are (1) to analyze the influence of family type, husband's education, wife's education, and the contribution of wife's income on the equality of decision making, (2) analyze the influence of family type, husband's education, wife's education, and contribution of wife's income on the level of ownership of goods valuable, (3) analyzing the role of equality in decision making in mediating the influence of family type, husband's education, wife's education, and wife's income contribution on the level of ownership of valuable goods, (4) analyzing the difference in equality of decision making and the level of ownership of valuables in households according to position female ASN echelon in Denpasar City. The data used are primary data, with a sample of 78 Female ASNs with a disproportionate startified random sampling method. The analysis technique used is path analysis. The results showed (1) nuclear family, husband's education, wife's education, and wife's income contribution had a positive effect on equality of decision making, (2) nuclear family, husband's education, wife's education, and wife's income contribution had a positive effect on the level of ownership of valuable goods, (3) equality of decision making mediates the effect of nuclear family type on the level of ownership of valuable goods in the household, (4) there is a significant difference in the equality of decision making and the level of ownership of valuables in the household according to the position of echelon ASN Perempuan in Denpasar City. Keywords : Equality, Decision Making, Ownership of Valuables